2018
DOI: 10.1186/s41200-018-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

First record of Echinothrix calamaris (Echinoidea: Diadematidae) in the Colombian Pacific

Abstract: Background: The occurrence of Echinothrix calamaris Pallas, 1774 is reported for the first time in Colombia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…Lo anterior puede deberse a un patrón real o a un menor esfuerzo de investigación en la costa Pacífica de Colombia. Recientemente, Muñoz y Londoño-Cruz (2016) y Londoño-Cruz et al (2018) registraron la presencia de dos especies de equinoideos en la isla Gorgona, lo que incrementa el número de especies conocidas para esta área protegida a 41.…”
unclassified
See 1 more Smart Citation
“…Lo anterior puede deberse a un patrón real o a un menor esfuerzo de investigación en la costa Pacífica de Colombia. Recientemente, Muñoz y Londoño-Cruz (2016) y Londoño-Cruz et al (2018) registraron la presencia de dos especies de equinoideos en la isla Gorgona, lo que incrementa el número de especies conocidas para esta área protegida a 41.…”
unclassified
“…It can be due to a real pattern or to less research effort on the Pacific coast of Colombia. Recently, Muñoz and Londoño-Cruz (2016) and Londoño-Cruz et al (2018) reported the presence of two species of echinoids in Gorgona Island, increasing the number of known species to 41 for this protected area.…”
mentioning
confidence: 99%
“…En su capítulo, Bouchet (2006) argumenta que los grupos más comunes de organismos marinos, como los moluscos, están alcanzando su número estimado de especies, pero en una publicación más reciente, Bouchet et al (2016) mencionan que el número de nuevas especies de moluscos que todavía faltan por describir es tres veces mayor que el número actual de especies conocidas y descritas (150 000 vs. 50 000) y que, al ritmo actual, tomaría al menos 300 años nombrar todos los moluscos que habitan el planeta. Por lo tanto, incluso en grupos bien conocidos, no es raro encontrar registros de especies nuevas para la ciencia (v. g. Tan and Liu, 2001;Tamsouri et al, 2014) o documentar la extensión de los rangos de distribución -nuevos registros regionales (v. g. Valencia-Giraldo et al, 2015;Muñoz and Londoño-Cruz, 2016;Londoño-Cruz et al, 2018), en regiones donde escasean especialistas, esfuerzos de investigación o ambos.…”
unclassified
“…In his chapter, Bouchet (2006) argues that the most common groups of marine animals, like the mollusks, are reaching their estimated number of species, but in a more recent publication, Bouchet et al (2016), mention that the number of new species of mollusks yet to be described is three times larger than the current number of known and described species (150 000 vs. 50 000) and that at the current pace, it will take at least 300 years to name all the mollusks inhabiting the planet. Hence, even in well-known groups, it is not rare to find records of species new to science (e.g., Tan and Liu, 2001;Tamsouri et al, 2014) or to document the extension of species' range distributions -new regional records (e.g., Valencia-Giraldo et al, 2015;Muñoz and Londoño-Cruz, 2016;Londoño-Cruz et al, 2018), in regions where specialists or research efforts or both are scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation